Pedunculopontine Nucleus Dysconnectivity Correlates With Gait Impairment in Parkinson’s Disease: An Exploratory Study - Joza, Stephen; Camicioli, Richard; Martin, W. R. Wayne; Wieler, Marguerite; Gee, Myrlene; Ba, Fang (Frontiers in Aging Neuroscience, 2022)
BACKGROUND: Gait impairment is a debilitating and progressive feature of Parkinson’s disease. Increasing evidence suggests that gait control is partly mediated by cholinergic signaling from the pedunculopontine nucleus. OBJECTIVE: We investigated whether pedunculopontine nucleus structural connectivity correlated with quantitative gait measures in Parkinson’s disease. METHODS: Twenty Parkinson’s disease patients and 15 controls underwent diffusion tensor imaging to quantify structural connectivity of the pedunculopontine nucleus. Whole brain analysis using tract-based spatial statistics and probabilistic tractography were performed using the pedunculopontine nucleus as a seed region of interest for cortical and subcortical target structures. Gait metrics were recorded in subjects’ medication ON and OFF states, and were used to determine if specific features of gait dysfunction in Parkinson’s disease were related to pedunculopontine nucleus structural connectivity. RESULTS: Tract-based spatial statistics revealed reduced structural connectivity involving the corpus callosum and right superior corona radiata, but did not correlate with gait measures. Abnormalities in pedunculopontine nucleus structural connectivity in Parkinson’s disease were lateralized to the right hemisphere, with pathways involving the right caudate nucleus, amygdala, pre-supplemental motor area, and primary somatosensory cortex. Altered connectivity of the right pedunculopontine nucleus-caudate nucleus was associated with worsened cadence, stride time, and velocity while in the ON state; altered connectivity of the right pedunculopontine nucleus-amygdala was associated with reduced stride length in the OFF state. CONCLUSION: Our exploratory analysis detects a potential correlation between gait dysfunction in Parkinson’s disease and a characteristic pattern of connectivity deficits in the pedunculopontine nucleus network involving the right caudate nucleus and amygdala, which may be investigated in future larger studies